Radio over Fiber Systems in Cellular Communications: A Systematic Literature Review and Research Agenda - Irfan Mujahidin; Fahmi Baihaqi; Eni Dwi Wardihani (CYCLOTRON, 2023)
A technology combining wireless communications and fiber optics to transmit radio frequency signals via fiber optic networks is called the Radio Over Fiber system. Capacity, range, reliability, and flexibility of the communication system are advantages offered by this method. Converting RF signals to optical signals using an optical modulation technique is a basic principle of the RoF system, in which they are then transmitted over fiber optic cables. Then, with the use of an optic detector and demodulation technique, that signal is restored to an RF signal at the receiving end. In RoF systems, the reduction of power loss and signal amplification is achieved through optical fiber, which allows transmission over long distances without loss of signal quality. Applications of the RoF system are cellular networks, satellite communications, and remote sensors. In cellular networks, the application of RoF such as expanding cellular network coverage, wireless backhaul, and increasing network capacity. In range expansion, RoF enables the transmission of RF signals from a base station to a remote receiving station via optical fiber, overcoming distance barriers and signal attenuation that occurs in traditional RF transmission. In wireless backhaul, RoF is used to connect base stations with the core network via optical fiber, providing higher capacity and reliability compared to traditional wireless backhaul. To increase network capacity, RoF can move its signal processing and amplifier toward the final users to enhance the data speeds and capacities of cellular networks. It is intended that readers will be able to learn more about Radio Over Fiber systems and their potential for improving the performance of a wireless radio network, as well as how this technology can increase its signal quality when it comes to mobile communications. With the continuous development of RoF technology, it is expected that there will be significant improvements to cellular communication services in the future.